2021
DOI: 10.1556/2060.2021.00182
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic interval training improves irisin and chemerin levels of both liver and visceral adipose tissues and circulating asprosin in rats with metabolic syndrome

Abstract: The perturbation of adipokinetic hormones, such as irisin, chemerin, and asprosin has been reported to participate in pathological conditions (e.g., insulin resistance) and chronic inflammation. However, exercise training has been long established as an effective intervention for prevention and treatment of these chronic and metabolic diseases. This study was to examine the effects of aerobic continuous training (ACT) and aerobic interval training (AIT) on irisin and chemerin levels of liver tissue (LT) and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Additionally, we were able to show that irisin concentrations were modulated in a dependent manner, considering the different depots of white adipose tissue analyzed. Another study conducted with Wistar rats demonstrated that eight weeks of continuous and interval aerobic training resulted in a significant increase in irisin concentration in visceral AT, showing the effectiveness of this type of training in modulating irisin, which is related to risk factors for metabolic syndrome [ 18 ]. However, Rocha-Rodrigues et al [ 19 ] demonstrated that aerobic training for eight weeks did not change irisin concentration in Sprague Dawley rats with obesity induced by a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we were able to show that irisin concentrations were modulated in a dependent manner, considering the different depots of white adipose tissue analyzed. Another study conducted with Wistar rats demonstrated that eight weeks of continuous and interval aerobic training resulted in a significant increase in irisin concentration in visceral AT, showing the effectiveness of this type of training in modulating irisin, which is related to risk factors for metabolic syndrome [ 18 ]. However, Rocha-Rodrigues et al [ 19 ] demonstrated that aerobic training for eight weeks did not change irisin concentration in Sprague Dawley rats with obesity induced by a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%